Financial hardship assistance behind the scenes: Insights from financial counsellors. Issue 3 (22nd August 2017) - Ali, Paul; Bourova, Evgenia; Ramsay, Ian
Abstract: Financial hardship, in a credit society such as Australia, can affect almost anyone. To protect consumers from the negative impacts of financial hardship—which can include the stresses of enforcement action and disconnection from essential services—legal protections have been incorporated into the regulatory frameworks for the consumer credit, energy, water and telecommunications sectors. In this article, we outline the findings of our study, which used a survey of financial counsellors around Australia and focus group interviews with Victorian financial counsellors to examine how these legal protections are being implemented by service providers in these four sectors. Our findings highlight a tendency on the part of service providers to take a generic, one‐size‐fits‐all approach to compliance with these legal protections that prevents them from effectively assisting consumers struggling with debt. We discuss the particular shortcomings of this approach in the context of consumers living on low incomes—especially Centrelink incomes—and outline the policy implications of our findings for assisting these vulnerable groups.